Analysis of Levels of Phosphorus and Magnesium in Beef Bones from Kaledo Waste - Isnawiyah, Nurzaida; Hamzah, Baharrudin; Aminah , Sitti; Tiwow, Vanny M. A.; Hardani , Ririen (Jurnal Akademika Kimia, 2024)
The Kaili tribe is a tribe with a very distinctive and well-known culinary heritage in Indonesia, one of which is Kaledo (donggala soft leg). The large number of restaurants and restaurants that provide Kaledo menus raises problems, namely the lack of utilization of beef bones from Kaledo waste, causing environmental issues. The community does not know much about the types of minerals contained in the beef bones. Among them are the minerals contained in beef bones, namely phosphorus and magnesium. This study aims to determine the levels of phosphorus and magnesium in beef bones from Kaledo waste taken randomly from Kaledo restaurants in Palu City. Determination of phosphorus and magnesium levels in beef bones from Kaledo waste using a Uv-Vis spectrophotometer and an atomic absorption spectrophotometer (AAS). The results showed that the analysis of the phosphorus content of beef bones from Kaledo waste obtained 95.125 mg / 100 g, and the magnesium content was 102.9 mg / 100 g. The results of this study are expected to be a source of information about the levels of phosphorus and magnesium contained in beef bones from Kaledo waste and can be used further as a substance in the utilization of beef bones from Kaledo waste.